Navigating Challenges in the Dairy Industry: A Case Study on Gomati Cooperative Milk Producers Union Limited (GCMPUL) - Dey, Trinankur (AMC Indian Journal of Entrepreneurship, 2024)
Fishing, farming, dairying, pig farming, and sericulture are all part of the multi-sectoral agricultural sector that adds to the gross state domestic product (GSDP); among them is the dairy industry, which is one of the most significant, with India being the world’s largest milk producer. India produced 221 million tonnes of milk by 2021–2022, a significant increase from 138 million tonnes in 2013–2014. In addition, the average person has far more milk than the rest of the world. Due to the growing demand, many companies have introduced processed dairy products in the market. Established in 1982 with the objective of establishing and developing the dairy sector, Gomti Cooperative Milk Producers Union Limited (GCMPUL) has contributed immensely to the north-eastern state of Tripura. GCMPUL supported local dairy producers by ensuring fair prices, providing technical assistance, and improving their standard of living. Despite limited resources, GCMPUL has shown remarkable growth in both market penetration and milk production. However, it faces challenges such as a lack of variety in its supply chain, outdated manufacturing facilities, and competition from well-known brands. GCMPUL needed to innovate, improve its marketing strategy, and also enter unexplored markets like Bangladeshi exports to sustain and expand. Local dairy producers would be empowered, and rural Tripura could experience socio-economic growth by resolving these issues and utilizing its benefits.